Contrast enhanced ultrasound (CEUS) imaging of solid benign focal liver lesions. (4th May 2018) - Dietrich, Christoph F.; Tana, Claudio; Caraiani, Cosmin; Dong, Yi
ABSTRACT: Introduction : Ultrasound is well accepted worldwide for imaging of the liver. Absences of radiation exposure, low cost and large diffusion are some of the advantages that make this technique the first to be used in the assessment of focal liver lesions (FLL). Areas covered : Contrast enhanced ultrasound (CEUS) has been introduced more than twenty years ago, and its detection rate is comparable to that of contrast enhanced magnetic resonance imaging (CEMRI) and contrast enhanced computed tomography (CECT). In this narrative review, we discuss the main CEUS features of benign liver lesions and controversies in published results including the gold standard chosen and the quality and knowledge of the preferred techniques. Expert commentary : CEUS is safe and allows an immediate evaluation of the nature of FLL. CEUS permits differentiation between malignant and benign FLL in healthy liver parenchyma by analysing the arterial, portal venous and late phases. CEMRI and CECT are reliable to characterize FLL but higher costs, radiation exposure, nephrotoxicity (in particular for CECT) and absence of real time imaging limit the appropriate evaluation of FLL. Therefore CEUS can be preferred in most clinical situations, and when results are unclear or suggestive for malignant FLL, biopsy and histological examination can be directly initiated avoiding unnecessary additional imaging.